Integrating IPACK (Interspace between the Popliteal Artery and Capsule of the Posterior Knee) Block in an Enhanced Recovery after Surgery Pathway for Total Knee Arthroplasty—A Prospective Triple-Blinded Randomized Controlled Trial - BH, Poonam Pai; Jinadu, Samiat; Okunlola, Olubunmi; Darkzali, Haider; Lin, Hung Mo; Lai, Yan H. (The Journal of Knee Surgery, 2022)
We explored the efficacy of an interspace between the popliteal artery and capsule of the posterior knee (IPACK) block when added to an established enhanced recovery after surgery (ERAS) pathway to assist with posterior knee analgesia and functional mobility after total knee arthroplasty (TKA). We recruited participants undergoing TKA in our prospective, randomized, triple-blinded controlled trial. All study patients participated in our ERAS pathway consisting of a primary spinal anesthetic, adductor canal nerve catheter, and periarticular joint infiltration. Patients were randomized to receive an IPACK block or no block. The primary outcome was total postoperative opioid consumption. Secondary outcomes included pain scores, recovery unit length of stay, time to first opioid use, the incidence of posterior knee pain, ambulation distance and activities of daily living on postoperative day 1, and hospital length of stay. A total of 96 patients were randomized to the control and IPACK groups. There were no statistical differences in primary or majority of secondary outcomes. There was a lower incidence of posterior knee pain (39%) in the IPACK group when compared with controls (8.7%), p < 0.01. In terms of opioid consumption and a majority of functional outcomes, our study demonstrates no overall benefits of adding an IPACK block in this ERAS pathway in TKA. Nevertheless, IPACK may have the potential of mitigating posterior knee pain after TKA. Level of evidence: level 1.Clinical trial number and registry URL: NCT03653416. www.clinicaltrials.gov.
Keywords: IPACK block; total knee arthroplasty (TKA); adductor canal block (ACB); enhanced recovery after surgery (ERAS)